2022
DOI: 10.3390/biomedicines10092208
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Patterns in taVNS: A Systematic Review

Abstract: Transcutaneous auricular vagus nerve stimulation (taVNS) is a newer delivery system using a non-invasive stimulation device placed at the ear. taVNS research is focused on clinical trials showing potential therapeutic benefits, however the neurophysiological effects of this stimulation on brain activity are still unclear. We propose a systematic review that aims to describe the effects of taVNS on EEG measures and identify taVNS parameters that can potentially lead to consistent EEG-mediated biomarkers for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Even though there are several methods to explore the impact of antipsychotic drugs on brain functional connectivity in preclinical models, two are the most widely applied: functional magnetic resonance imaging (fMRI) and, on the other hand, electrophysiology/electroencephalogram (EEG), which assess interregional patterns of co-activation and neuronal synchrony by measuring brain blood flow and electrical activity, respectively [ 114 , 115 , 116 ].…”
Section: Methods To Study Brain Functional Connectivity In Translatio...mentioning
confidence: 99%
“…Even though there are several methods to explore the impact of antipsychotic drugs on brain functional connectivity in preclinical models, two are the most widely applied: functional magnetic resonance imaging (fMRI) and, on the other hand, electrophysiology/electroencephalogram (EEG), which assess interregional patterns of co-activation and neuronal synchrony by measuring brain blood flow and electrical activity, respectively [ 114 , 115 , 116 ].…”
Section: Methods To Study Brain Functional Connectivity In Translatio...mentioning
confidence: 99%
“…Various neurophysiological metrics have been studied as potential biomarkers of tVNS and have recently been extensively reviewed. 81 While there has been interest in the P300 event-related potential as a marker of LC-noradrenergic signaling, this has not reliably been found to change with taVNS. 72 Fifth, tVNS should be paired with different rehabilitative strategies to target specific domains of upper limb function such as strength training, dexterity tasks, passive stretching, and sensory training to identify which aspects of arm function respond most favorably to tVNS.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…For instance, a recent systematic review performed by our group has demonstrated the taVNS electroencephalographic effects current stage of evidence and the lack of homogenous studies and standardized metrics in the field. 9 Thus, well designed, and multimodal mechanistic studies to explore the ways that taVNS works are required. A possible mechanism that has been studied recently is the modulatory effects of vagus stimulation in the cholinergic anti-inflammatory pathway, the microbiota-gut-brain axis, or the hypothalamic-pituitary-adrenal axis.…”
Section: Future Perspectives Of Avnsmentioning
confidence: 99%
“…7,8 Recent systematically reviewed results, on the aVNS's electroencephalographic effects, suggests the capability of aVNS in modulate cortical activity. 9 Furthermore, aVNS has been investigated in a variety of conditions, such as epilepsy, tinnitus, depression, Alzheimer's disease, Schizophrenia, pain, migraine, and Parkinson's disease, being considered safer, more accessible, and less invasive alternative than the surgical device. [9][10][11][12] Currently, animal studies seem to be having positive results regarding the reestablishment of motor function in rats with post stroke sequelae after aVNS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation